All that glitters is not gold. Effects of working from home on income inequality at the time of COVID-19 - Luca Bonacini; Giovanni Gallo; Sergio Scicchitano (Global Labor Organization (GLO), 2020)
The recent global COVID-19 pandemic forced most of governments in developed countries to introduce severe measures limiting people mobility freedom in order to contain the infection spread. Consequently, working from home (WFH) procedures became of great importance for a large part of employees, since they represent the only option to both continue working and keep staying home. Based on influence function regression methods, our paper explores the role of WFH attitude across labour income distribution in Italy. Results show that increasing WFH attitudes of occupations would lead to a rise of wage inequality among Italian employees. Specifically, a change from low to high WFH attitude would determine a 10% wage premium on average and even higher premiums (+17%) in top deciles of wage distribution. A possible improvement of occupations WFH attitude tends to benefit male, older and high-paid employees, as well as those living in provinces more affected by the novel coronavirus.
Keywords: D31; I18; J16; 330; COVID-19; working from home; inequality; unconditional quantile regressions